2017
DOI: 10.18321/ectj286
|View full text |Cite
|
Sign up to set email alerts
|

Spongy Structures Coated with Carbon Nanomaterials for Efficient Oil/Water Separation

Abstract: Rapid progress of processing and transportation of oil and petroleum products may cause disaster for environment like oil spill. Oil booms, combustion, and oil skimmer vessels are usually used to clean up the oil spill, but often with poor efficiency and even with undesirable environmental side effects. With obtaining of carbon nanomaterials (CNMs) (graphene, carbon nanotubes) and developing inexpensive technologies for their synthesis it has become perspective to use them for creation of 3D structures which m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
6
0
2
Order By: Relevance
“…Organic dyes are used on a large scale in modern industries. Wastewater polluted with such substances subsequently leads to environmental problems [ 66 , 67 ]. This is due to the fact that most organic dyes consist of biodegradable aromatic structures and azo-groups.…”
Section: The Utilization Of Photocatalysts Based On Tio mentioning
confidence: 99%
“…Organic dyes are used on a large scale in modern industries. Wastewater polluted with such substances subsequently leads to environmental problems [ 66 , 67 ]. This is due to the fact that most organic dyes consist of biodegradable aromatic structures and azo-groups.…”
Section: The Utilization Of Photocatalysts Based On Tio mentioning
confidence: 99%
“…In previous studies, we have shown that HAP has a positive effect on migration, proliferation, and differentiation of cells and their bonding to scaffold, which was prepared in the form of a matrix based on polymer nanosized fibers with the addition of HAP particles [29][30][31][32][33][34]. Based on the obtained in our studies results, as well as on the studies carried out in experimental works devoted to the study of biological scaffolds [35][36][37], fabricated by 3D printing technology, we modeled composite scaffolds with different types of structures, and the significant difference between the indicated above studies and our model was the content of HAP, which in our scaffolds did not exceed 10%.…”
Section: Results Of Internal Flow Modelingmentioning
confidence: 99%
“…Today, economically competitive SOFC systems already exist, apparently ready for commercialization, but the widespread penetration of the technology into the market requires constant innovation of materials and manufacturing processes to increase the system service life and reduce the costs [9]. Among the numerous types of FC, such as alkaline FC [10,11], FCs with proton-exchange membrane [12][13][14], FCs based on carbon compounds [15,16], solid oxide fuel cells (SOFCs) based on oxygen-conducting solid electrolytes, which have a high efficiency (up to 60%) and can use not only pure hydrogen but also various hydrocarbons as a fuel, should be highlighted. The main structural components of these SOFCs are porous electrodes (anode and cathode) and a solid gas-tight electrolyte (ZrO 2 : Y 2 O 3 (YSZ)) located between them [1].…”
Section: Introductionmentioning
confidence: 99%
“…Water and CO 2 are the main reaction products on the anode part. The known most effective material for the creation of anodes is the so-called "cermet", which is a composite based on Ni (or NiO) and YSZ [9,[8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%